2020
DOI: 10.3389/fspor.2020.00034
|View full text |Cite
|
Sign up to set email alerts
|

Exercise in Sub-zero Temperatures and Airway Health: Implications for Athletes With Special Focus on Heat-and-Moisture-Exchanging Breathing Devices

Abstract: Asthma is highly prevalent among winter endurance athletes. This “occupational disease” of cross-country skiers, among others, was acknowledged during the 1990s, with the pathogenesis attributed to repeated and prolonged exposure to cold, dry air combined with high rates of ventilation during exercise. Nevertheless, more than 25 years later, the prevalence of asthma among Scandinavian cross-country skiers is unchanged, and prevention remains a primary concern for sports physicians. Heat-and-moisture-exchanging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 75 publications
1
15
0
Order By: Relevance
“…The effects of cold climate are subsequently modified by individual factors, of which the degree of physical activity is likely the most important, since physical strain induces a higher respiratory rate, and a shift to mouth breathing, which increases the exposure of the airways to cold and dry air (Koskela 2007;McFadden et al 1985). In fact, experimental studies show that high exercise intensity in a cold climate can induce lung function reduction in healthy individuals (Hanstock et al 2020). The use of personal protection equipment, such as hooded jackets, and heat-and moisture-exchanging breathing devices, has been shown to alleviate exercise-induced asthma and other respiratory symptoms during physical activity in cold air (Frischhut et al 2020;Jackson et al 2020;Koskela 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of cold climate are subsequently modified by individual factors, of which the degree of physical activity is likely the most important, since physical strain induces a higher respiratory rate, and a shift to mouth breathing, which increases the exposure of the airways to cold and dry air (Koskela 2007;McFadden et al 1985). In fact, experimental studies show that high exercise intensity in a cold climate can induce lung function reduction in healthy individuals (Hanstock et al 2020). The use of personal protection equipment, such as hooded jackets, and heat-and moisture-exchanging breathing devices, has been shown to alleviate exercise-induced asthma and other respiratory symptoms during physical activity in cold air (Frischhut et al 2020;Jackson et al 2020;Koskela 2007).…”
Section: Discussionmentioning
confidence: 99%
“…From a population-based perspective, temperatures ranging from − 7 to − 18 °C have been reported to provoke airway symptoms (Harju et al 2010). For winter endurance sports, temperature limits between − 16 and − 25 °C have been used, but have proven insufficient to prevent airway symptoms (Hanstock et al 2020). More research, with both laboratory and epidemiological approach, is needed to establish temperature thresholds for adverse respiratory health effects.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, +10°C has been shown to be optimal for preventing thermoregulatory stress, and close to an “optimal” temperature for endurance exercise performance [ 47 ]. Most experimental exposure studies evaluating lung function responses to subzero air have used +20°C as control exposure [ 48 ]. Pekkarinen et al did not detect any lung function impairments in healthy males exposed to room temperature and 0°C [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there may be some rationale for increased usage of HME during low‐intensity training; however, neither study was performed in a cold environment. The majority of studies that have been conducted in sub‐zero environments have shown that higher exercise intensities more commonly induce reductions in lung function in healthy individuals 25 . Further work is required to investigate the effects of different training modalities on airway function in healthy skiers and skiers with asthma, in order to make recommendations about when it is most appropriate to employ preventive strategies.…”
Section: Discussionmentioning
confidence: 99%